(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Epicardial fat is one of the most discussed and unexplored risk factor for cardiovascular disease. Structure of epicardial adipose tissue, it’s functions and pathophysiological processes are observed. It is considered epicardial fat to increase cardiovascular risk. Currently, there is no standardized methodology for measuring the thickness of the epicardial fat. As the most accessible method, the method of transthoracic echocardiography is considered and described.